EMPLOYEE RETENTION & PERFORMANCE MANAGEMENT IN INDIAN PRIVATE BANKS (International Journal of Food and Nutritional Sciences, 2022)
One of the most significant challenges that organisations are currently confronted with is that of managing employee performance and retaining valuable employees. The banking industry is another sector that is impacted by this issue. The purpose of this study is to gain an understanding of, conduct an analysis of, and make comparisons regarding the performance management and retention strategies utilised by ICICI bank and Kotak Mahindra bank. The banks have implemented a variety of cutting-edge initiatives, such as career-related growth opportunities, compensation-related benefits, retirement planning benefits, performance-based appraisal strategies, and other similar initiatives. The conceptual variable-based model that has been framed has been done so for the purpose of the study, as well as for the purpose of better understanding the performance management and retention strategies. After conducting an analysis of the data, the conclusion that can be drawn is that both ICICI Bank and Kotak Mahindra Bank take the same approach to the management of employee performance and retention. The purpose of the research was to identify and rank the factors that contribute to employee retention as well as performance management at ICICI bank and Kotak Mahindra banks. It is possible to summarise that the perspectives of both banks' employees are the same with regard to the variables of employee retention and performance management. One of the most important goals of the study was to analyse and contrast the retention and performance management strategies utilised by the sampled banks. In the research project, the ANOVA statistical test was utilised to perform the comparison analysis. It is possible to draw the conclusion that the retention strategies of the banks that were sampled are identical.